Modelo de Competencias para el Cambio Individual = Model of competence for individual change. - Aldape, T. (Universidad Autónoma de Nuevo León, 2007)
Abstract. This essay proposes a model for the development of individual competences to change, to allow the possibility for employees to be better prepared to quickly and effectively adapt themselves to today’s uncertain and changing circumstances, which is fundamental to organization’s competitive advantage and success.